Characteristics Morphology and Morphometry Lepidotrigona terminata (Hymenoptera: Meliponini) in Central Sulawesi - Nur Hikmah; I Made Budiarsa; Fatmah Dhafir; Mursito S. Bialangi; Masrianih; Manap Trianto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Stingless bees are eusocial bees belonging to the Apidae family and the Meliponini subfamily. This study aims to describe the morphological and morphometric and nest structure characteristics of Stingless bee Lepidotrigona terminata from Parigi Moutong Regency. This study used the roaming method with a purposive sampling technique. Obtained morphological and morphometry data were analyzed using the Principal Component Analysis (PCA) method with PAST4 software. The morphological characters of Lepidotrigona terminata had a dominant black body, on the thorax, black scutum and scutellum covered with brown hair and yellow packaging on the edges. The tegula is brown, the tibia on the legs is black, the hind tibia is slightly hairy (plumose), antennae with 11 flagellomeres, the number of hamuli is 8. The most dominant character in the formation of seven groups of stingless bees in this study were Hamuli Number (HN), Fore Wing Length (FWL), and Length of Forewing Including Tegula (WL1). There are differences in character size compared to the same or different species in other areas.